Titanium particles: An emerging risk factor for peri-implant bone loss - Zoë Berryman; Laura Bridger; Haizal Mohd Hussaini; Alison M. Rich; Momen Atieh; Andrew Tawse-Smith (Elsevier, 2020)
Objective: To investigate the presence of titanium particles in peri-implant tissues in cases diagnosed with peri-implantitis, and to identify immunological reactions that these particles may elicit. Methods: Ten peri-implant tissue biopsies of patients diagnosed clinically and radiographically with peri-implantitis were obtained from the archives of Oral Pathology Centre, University of Otago. The inclusion criteria involves: bleeding on probing, ≥6 mm probing depth and ≥3 mm radiographic bone loss around the dental implant. Peri-implant tissue samples were evaluated using scanning electron microscopy-energy dispersive x-ray spectroscopy (SEM-EDS) to identify of sites with/without titanium particles. Antibodies against human transforming growth factor beta 1 (TGF-β1), receptor activator of nuclear factor kappa-B ligand (RANKL), interleukin 33 (IL-33) and cluster of differentiation 68 (CD68) were used to stain the specimens. ImageJ software was used to standardise the sampling area, compare and characterise the inflammatory infiltrate in tissues with/without titanium particles. Inflammatory cytokines positivity was assessed using the immunoreactive scores (IRSs). Results: Light microscopy and SEM-EDS analysis identified titanium wear particles in 90% of the tissue samples, associated with a mixed chronic inflammatory infiltrate. Quantification analysis of RANKL revealed significantly higher IRS and intensity scores (p < 0.05) in areas containing titanium. High intensity, proportion and IRSs of TGF-β1 and IL-33 were observed in areas with titanium. CD68 had higher IRSs in the absence of titanium particles. Conclusions: Significant overexpression of the cytokine RANKL was observed, with a trend for over-expression of IL-33 and TGF-B1 in areas with titanium. Further studies with large sample size and appropriate control group for quantification analysis is needed to confirm the role of titanium particles in initiating bone loss.